2021
DOI: 10.21203/rs.3.rs-142805/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic Control of Iron Bioavailability is Independent from Iron Concentration in a Diverse Winter Wheat Mapping Population

Abstract: Background: Anemia is thought to affect up to 1.6 billion people worldwide. One of the major contributors to low iron (Fe) absorption is a higher proportion of cereals compared to meats and pulse crops in people’s diets. This has now become a problem in both the developed and developing world, as a result of both modern food choice and food availability. Bread wheat accounts for 20% of the calories consumed by humans and is an important source of protein, vitamins and minerals meaning it could be a major vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…The foremost reason for this is that even though Fe content in the whole seed is increased, it is stored in the aleurone layer which gets removed while milling, leaving only the endosperm for consumption. Therefore, both Fe content and bioavailability should be taken into account while addressing the biofortification of wheat (Eagling et al, 2014;Wright et al, 2021). To further address this, the wheat genome was studied for the identification of the QTLs that could be responsible for both high Fe-content and bioavailability (Wright et al, 2021).…”
Section: Enhancing Grain Fe Bioavailabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The foremost reason for this is that even though Fe content in the whole seed is increased, it is stored in the aleurone layer which gets removed while milling, leaving only the endosperm for consumption. Therefore, both Fe content and bioavailability should be taken into account while addressing the biofortification of wheat (Eagling et al, 2014;Wright et al, 2021). To further address this, the wheat genome was studied for the identification of the QTLs that could be responsible for both high Fe-content and bioavailability (Wright et al, 2021).…”
Section: Enhancing Grain Fe Bioavailabilitymentioning
confidence: 99%
“…Therefore, both Fe content and bioavailability should be taken into account while addressing the biofortification of wheat (Eagling et al, 2014;Wright et al, 2021). To further address this, the wheat genome was studied for the identification of the QTLs that could be responsible for both high Fe-content and bioavailability (Wright et al, 2021). Very recently, a two-gene strategy to overexpress VIT-NAS in wheat endosperm showed high Fe concentration and also improves mineral bioaccessibility (Harrington et al, 2022).…”
Section: Enhancing Grain Fe Bioavailabilitymentioning
confidence: 99%
“…It is often reported that phytate inhibits Fe bioavailability, so the negative correlation between Fe and phytate levels in teff could prove bene cial. While future research is requiredto determine whether elevated levels of phenolics that stimulate and inhibit Fe uptake in the human gut can help alleviate the anaemia seen in Ethiopian children [69], the signi cance of the SNP in the teff F3'H gene Et_s3159-0.29-1.mrna1,which explainsa large proportion of the variation in kaempferol glycoside and quercetin glycoside levels, suggest this might be a breeding target to improve Fe bioavailability in teff, as kaempferol glycoside is known to promote Fe absorption while quercetin glycoside inhibits Fe absorption in cell assays [60].In addition, phenolic compounds have also been found to in uence other agronomic traits, including tolerance to both biotic and abiotic stress [14,60,61,68].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advancements in our understanding of the genetics of teff include a fairly complete genome assembly, the release of gene models,as well as a number of RNASeq datasets which are all publicly available [9]. These allow for translation of knowledge on grain forti cation from other species, supporting more rapid advancements in efforts to improve the nutritionalpotentialofteff [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%